Penelusuran Epistemologi Kekadiman Alam dalam Tahafut Al-Falasifah dan Tahafut Al-Tahafut - Marzuki, M Fathin Shafly; Wildan, Raina; Rijal, Syamsul (Program Studi Aqidah dan Filsafat Islam, 2023)
This study aims to explore the epistemological debate between Al-Ghazali and Ibn Rushd concerning the concept of the eternity of the world within Islamic philosophy, highlighting the relevance and depth of their thoughts in contemporary Islamic intellectual discourse. Al-Ghazali, through his work